Ways of Choirmaster Art Development in Azerbaijan - Лейла Залієва (Вісник Київського національного університету культури і мистецтв. Серія: Музичне мистецтво, 2021)
The article is devoted to the history of the choral music development in Azerbaijan and to highlighting the ways of choirmaster art formation. The development of choral art in Azerbaijan began, firstly, with the formation of the composer creative activity. The introduction of classical choral samples with the emergence of the first opera and the formation of an ensemble for performing it are considered to be the first step in this area. Later, the emergence of professional choral collectives, the development of the opera genre, as well as the activity of music education institutions included a new stage of development. Therefore, the formation of choral music genres allowed the development of the art of conducting, especially the areas such as an opera choirmaster who leads a choir collective, a chapel choirmaster.